Rural Community Empowerment: Sustainable Development Practices in Sumbermanjingkulon Village, Indonesia - Wahyunie, Itha Aning; Praptining Sukowati; I Made Weni; Eny Haryati (International Journal of Technology and Education Research, 2025)
This research aims to analyze the challenges faced by rural communities in Sumbermanjingkulon Village, Indonesia, including limited public facilities, minimal health services, and inadequate educational resources. The research explores the importance of community participation and self-reliance in village development, emphasizing the active involvement of residents in contributing resources to infrastructure projects. In addition, the research highlighted the importance of traditional farming practices passed down through generations, demonstrating the strength of local knowledge and sustainable farming techniques in the village. The research also discussed collaborative efforts between village officials and residents in managing village funds, emphasizing the need for community involvement, utilization of local labor, and use of local resources for development projects. The research analyzed the economic potential of communal forest management and freshwater fisheries in improving community economic welfare while promoting environmental sustainability. The limitations faced by villages in terms of governance include the quality of resources and infrastructure that impact village development as well as the management of village funds.